2005
DOI: 10.1071/ah050051
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised controlled trial of an aged care nurse intervention within the Emergency Department

Abstract: The aim of this randomised controlled trial involving 224 elderly patients was to determine whether early geriatric assessment (in the form of an aged care nurse intervention based in the emergency department) reduced admission to the hospital, length of inpatient stay (LOS), or functional decline during the hospitalisation. Baseline geriatric assessments were recorded in the medical files of intervention patients (n = 114). The nurse also liaised with the patients' carers and health care providers, organised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…15 The implementation of these services was associated with a decrease in attendances by older mented in other parts of the country with varying success. [16][17][18][19][20][21][22] The quintessence of such services is an integrated, multidisciplinary approach to assist in the acute hospital and post-discharge care of older people at risk of repeated hospital presentations. The emphasis has been on returning these patients to and maintaining them in the community.…”
Section: Discussionmentioning
confidence: 99%
“…15 The implementation of these services was associated with a decrease in attendances by older mented in other parts of the country with varying success. [16][17][18][19][20][21][22] The quintessence of such services is an integrated, multidisciplinary approach to assist in the acute hospital and post-discharge care of older people at risk of repeated hospital presentations. The emphasis has been on returning these patients to and maintaining them in the community.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions are resource-intensive and have had only intermittent success in decreasing hospitalizations, reducing ED visits, increasing primary care visits, and improving functional outcomes. [7][8][9][10][11][12][13][14] Several studies have found that comprehension of discharge instructions is a significant barrier to care compliance [15][16][17][18] and that many older patients discharged from the ED do not understand their discharge instructions, nor do they attend follow-up appointments. 18,19 Studies conducted in other patient populations have shown that telephone follow-up encourages compliance with discharge instructions and increases the likelihood of physician follow-up.…”
mentioning
confidence: 99%
“…Three studies showed no advantage in performing CGA with regard to outcome (functional decline, ED readmission, institutionalization, death) (37,38,40). The other five studies showed a reduction in functional decline after CGA in ED (10,11,36,39,41).…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 93%
“…In the fi- nal phase, 4 studies regarding CGA efficiency were excluded because of lack of a control or matched group. Lastly, we included 8 studies on CGA (10,11,(36)(37)(38)(39)(40)(41)) and 14 on screening tools (9, 41-53) (1 study belongs to both selections).…”
Section: Study Selection and Analysismentioning
confidence: 99%
See 1 more Smart Citation